Volume 3 2004
DOI: 10.1115/ht-fed2004-56770
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Rotor Tip Flow in a Highly Loaded Single-Stage Axial-Flow Pump Approaching Stall: Part II — Stall Inception — Understanding the Mechanism and Overcoming Its Negative Impacts

Abstract: When reaching the stall point of an axial-flow pump, the pump head characteristic becomes unstable and the pump head suddenly drops. Before this happens however, at even higher flow rates the NPSH3 and the pump body and shaft vibrations increase dramatically. For effectively increasing the available operating range, it is essential to find a solution for all three problems without reducing the pump efficiency at design. The paper describes an experimental investigation on the outlined subject that gives insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Goltz et al [2][3][4][5][6] showed the flow structures of a single-stage axial-flow pump from stable operation until deep stall. After the onset of stall, a short transient takes place.…”
Section: Previous Workmentioning
confidence: 99%
“…Goltz et al [2][3][4][5][6] showed the flow structures of a single-stage axial-flow pump from stable operation until deep stall. After the onset of stall, a short transient takes place.…”
Section: Previous Workmentioning
confidence: 99%
“…Design changes at the impeller inlet can be applied to reduce the effect of inlet recirculation and improve the instability in axial pumps, successfully. Instability can be reduced by adding grooves to the inlet (Goltz et al [24][25]) or a double-entrance structure (Flores et al [26], Cao and Li [27]).…”
Section: Introductionmentioning
confidence: 99%
“…Different geometries of the blade tip were employed to analyze the influence on cavitation characteristics. Goltz [14,15] investigated the structure of the rotor tip flow at different operating conditions. The spiral-type vortex breakdown was captured, which led to a rapid expansion of the clearance vortex in stream-wise, span-wise, and pitch-wise direction.…”
Section: Introductionmentioning
confidence: 99%